2018
DOI: 10.1016/j.celrep.2018.09.060
|View full text |Cite
|
Sign up to set email alerts
|

The p38α Stress Kinase Suppresses Aneuploidy Tolerance by Inhibiting Hif-1α

Abstract: SummaryDeviating from the normal karyotype dramatically changes gene dosage, in turn decreasing the robustness of biological networks. Consequently, aneuploidy is poorly tolerated by normal somatic cells and acts as a barrier to transformation. Paradoxically, however, karyotype heterogeneity drives tumor evolution and the emergence of therapeutic drug resistance. To better understand how cancer cells tolerate aneuploidy, we focused on the p38 stress response kinase. We show here that p38-deficient cells upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…This may be mediated by the p38α phosphorylation and inhibition of Drosha, a key enzyme in miRNA biogenesis whose downregulation sensitizes cells to stress 112 , or by phosphorylation and cytoplasmic translocation of the transcription factor TEAD, which impairs YAP activity, potentially reducing the expression of anti-apoptotic genes 113 . Moreover, p38α activation can induce other stress-induced deleterious effects, although substrates are not characterized, including mitochondrial malfunction 114 , decreased proteasome activity 115 and postmitotic apoptosis mediated by HIF1α inhibition and metabolic stress 116 .…”
Section: P38α Substrates and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be mediated by the p38α phosphorylation and inhibition of Drosha, a key enzyme in miRNA biogenesis whose downregulation sensitizes cells to stress 112 , or by phosphorylation and cytoplasmic translocation of the transcription factor TEAD, which impairs YAP activity, potentially reducing the expression of anti-apoptotic genes 113 . Moreover, p38α activation can induce other stress-induced deleterious effects, although substrates are not characterized, including mitochondrial malfunction 114 , decreased proteasome activity 115 and postmitotic apoptosis mediated by HIF1α inhibition and metabolic stress 116 .…”
Section: P38α Substrates and Functionsmentioning
confidence: 99%
“…Of course, target availability is not the only cell-specific factor that determines p38α function. For instance, p38α induces apoptosis when aneuploidy is induced in near-diploid HCT116 cancer cells that have robust mechanisms of genomic stability control 116 , whereas aneuploid cancer cells rely on p38α to engage DNA repair and facilitate survival 117 . It is therefore tempting to speculate that mechanisms linking aneuploidy with p38α-induced apoptosis might be non-operative in some cancer cells, and that the final fate of aneuploid cells may depend on the status of other DNA damage response proteins.…”
Section: Context-dependence Of P38α Signallingmentioning
confidence: 99%
“…However, these studies were limited to established human cell lines that were chromosomally stable and near diploid, such as RPE1, an hTERT-immortalized retinal pigmented epithelial cell line; HCT116, a colon carcinoma cell line; and a few other cell lines ( Cianchi et al, 1999 ; Giam et al, 2019 ; Hinchcliffe et al, 2016 ; Janssen et al, 2011 ; Kurinna et al, 2013 ; Li et al, 2010 ; Potapova et al, 2016 ; Santaguida et al, 2017 ; Soto et al, 2017 ; Thompson and Compton, 2010 ). Recent studies also revealed complex interplay between p53 and several other genome-protective proteins, such as p38, H3.3, and BCL9L ( Hinchcliffe et al, 2016 ; López-García et al, 2017 ; Simões-Sousa et al, 2018 ). However, it has been unclear whether a universal signal elicited by abnormal karyotypes may be sensed by the p53 pathway or whether karyotype-specific stress states are sensed through diverse mechanisms and converge upon p53 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence from experimental and clinical studies has revealed that the adaptability of cancer cells to hypoxia is closely related to cancer progression and contributes to the development of resistance to radiation and chemotherapy. [1][2][3][4][5][6] Hypoxia is a common feature of the tumor microenvironment that activates the HIF-signaling pathway in cancer cells. In the case of hypoxia, HIF is reported to be overexpressed in various cancer cells and associated with the progression and adverse clinical outcome of many different tumor entities, including colorectal cancer (CRC).…”
Section: Introductionmentioning
confidence: 99%